PENGARUH PENGANGGURAN, JUMLAH UANG BEREDAR, DAN SUKU BUNGA TERHADAP INFLASI DI NEGARA-NEGARA ASEAN - Ayu, Fransiska; Ridwan, Mochamad (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to analyze how unemployment, money supply, and interest rates impact inflation in eight ASEAN countries from 2017 to 2022. This study uses the Fixed Effect Model (FEM) as the optimal model to analyze the data, which reveals the significant impact of each independent variable on inflation in ASEAN countries. Through the panel data regression method, it was found in this study that the three variables simultaneously have an effect on inflation. Unemployment and interest rates have a partial negative correlation with inflation, while the money supply has a positive correlation. This finding is in line with the quantity theory of money and the Phillips curve, which shows that inflation has a negative relationship with unemployment and a positive relationship with the money supply.